Translating Emotion Through Imagery A Qualitative Analysis of Robert Frost’s The Road Not Taken - Fiona Djunita Natalia Luhulima; Andhyka Bhayangkara Asmara; Charista Syarani Bell; Naysilla Blessing Kolamban (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Robert Frost’s The Road Not Taken (1916) is one of the most frequently cited yet persistently misinterpreted poems in American literature. Popular readings often frame the poem as a celebration of individualism, overlooking its deeper engagement with ambiguity, memory, and emotional self-fashioning. This research paper examines how Frost employs imagery as a primary mechanism for translating complex emotional states into poetic experience. Using a qualitative interpretive methodology grounded in New Criticism and Affect Theory, the study conducts a close reading of key visual, auditory, and temporal images, such as the “two roads,” the “yellow wood,” the “undergrowth,” and the final “sigh.” The findings reveal that these images do not merely support the poem’s narrative but actively construct its emotional architecture, mediating ambivalence, nostalgia, regret, and retrospective rationalization. The study argues that Frost’s imagery exposes the tension between lived experience and remembered narrative, inviting readers to confront the human tendency to mythologize past choices. The paper contributes to literary studies by demonstrating how imagery functions as an affective translator rather than a decorative element, with implications for poetic interpretation, memory studies, and literature pedagogy.